"Diseño, construcción e implementación de un equipo de medidor de fuerzas de impacto (Péndulo charpy) para ensayos de resistencias de materiales de la Universidad Técnica Estatal de Quevedo-UTEQ" - Contreras Espinoza, Sixter David (2020)
The Quevedo state Tecnical University does not currentñy have an instrument yo carry out toughness tests, also known as a Cahrapy type impacts test. This test measures the amount of energy absorbed by material hen exposed to an impact and subsequient fracture. This test is standardizad by AST and code E-23. ..............................................................................................